Contrast-enhanced ultrasound for fetal and placental assessment: evidence, safety, and a roadmap for clinical translation - Jain, Alushika; Dhande, Rajasbhala P.; Parihar, Pratapsingh H.; Kashikar, Shivali; Raj, Nishant; Toshniwal, Amit (The Ultrasound Journal, 2025)
Background: Fetal growth restriction (FGR), preeclampsia, and other placental disorders are leading contributors to perinatal morbidity and mortality, primarily due to impaired uteroplacental perfusion. Existing imaging modalities, such as Doppler ultrasound and fetal MRI, provide indirect or limited functional insights into placental and fetal perfusion, constraining timely clinical intervention. Objective: To evaluate contrast-enhanced ultrasound (CEUS) as a promising, safe, and real-time tool for assessing placental perfusion and its potential application in maternal-fetal medicine through comprehensive analysis of methodological parameters, safety profiles, and emerging computational techniques. Methods: A comprehensive synthesis of preclinical and clinical studies was conducted, focusing on the safety, efficacy, and current use of CEUS in pregnancy. Key findings were drawn from animal models (rats, sheep, macaques) and human studies involving 256 pregnant individuals, with detailed analysis of imaging protocols, contrast agent characteristics, and quantification methods. Results: CEUS utilizes intravascular microbubble contrast agents (1–8 μm diameter) that do not cross the placental barrier, enabling safe maternal imaging. However, size distribution analysis reveals sub-micron populations (8–20% by number) requiring careful evaluation. Preclinical models confirm CEUS ability to detect placental perfusion Changes with 54% reduction in perfusion index following uterine artery ligation (p < 0.001). Human studies demonstrate zero clinically significant adverse events among 256 cases, though critical gaps exist including absent biomarker monitoring and long-term follow-up. Emerging AI-enhanced analysis achieves 73–86% diagnostic accuracy using ensemble deep learning architectures. Current limitations include significant protocol heterogeneity (MI 0.05–0.19, frequency 2–9 MHz) and absence of standardization. Conclusion: CEUS presents a compelling solution for perfusion imaging in pregnancy, offering functional, bedside imaging without fetal exposure to contrast agents. However, methodological limitations, knowledge gaps regarding long-term outcomes, and the distinction between conventional microbubbles and emerging nanobubble formulations demand systematic research investment. Clinical translation requires standardized protocols, comprehensive safety monitoring including biomarker assessment, ethical oversight, and long-term outcome studies to support integration into routine obstetric care.